2018
DOI: 10.4049/jimmunol.1800733
|View full text |Cite
|
Sign up to set email alerts
|

Cardiotrophin-like Cytokine Increases Macrophage–Foam Cell Transition

Abstract: CLCF1 is a neurotrophic and B cell-stimulating factor belonging to the IL-6 family. Mutations in the gene coding for CLCF1 or its secretion partner CRLF1 lead to the development of severe phenotypes, suggesting important nonredundant roles in development, metabolism, and immunity. Although CLCF1 was shown to promote the proliferation of the myeloid cell line M1, its roles on myeloid activation remain underinvestigated. We characterized the effects of CLCF1 on myeloid cells with a focus on monocyte-macrophage a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 43 publications
0
12
0
1
Order By: Relevance
“…is required for hematopoietic stem cell maintenance (33), a role that could involve bone marrow stromal cells, such as MSCs. CLCF1 administration was shown to promote B cell expansion and myelopoiesis (2,34,35). Ligands of CNTFR are believed to have direct and indirect effects on hematopoietic cells, such as B cells (2, 34 -36).…”
Section: Accelerated Communication: Clcf1 Modulates Msc Differentiationmentioning
confidence: 99%
“…is required for hematopoietic stem cell maintenance (33), a role that could involve bone marrow stromal cells, such as MSCs. CLCF1 administration was shown to promote B cell expansion and myelopoiesis (2,34,35). Ligands of CNTFR are believed to have direct and indirect effects on hematopoietic cells, such as B cells (2, 34 -36).…”
Section: Accelerated Communication: Clcf1 Modulates Msc Differentiationmentioning
confidence: 99%
“…CLCF1 is underexplored in comparison to CNTF but is highly prominent in lung adenocarcinoma, where it is secreted by cancer cells and cancer-associated fibroblasts to promote tumor through both autocrine and paracrine signaling (23,24). Furthermore, CLCF1 has also recently been shown to play a role in osteoporosis (25) and atherosclerosis (26). These studies highlight CNTFR and its ligands as targets for therapeutic intervention; a CNTFR agonist could potentially facilitate neuronal regeneration, while a CNTFR antagonist could inhibit this signaling axis for cancer or other disease treatment.…”
mentioning
confidence: 99%
“…The function of CLCF1 remains far from being understood. Recent studies have indicated that CLCF1 attend to modulate mesenchymal stem cell osteoblastic differentiation (26) and promote macrophage-foam cell transition (27). For kidney diseases, CLCF1 has been reported to trigger the recurrence of FSGS after kidney transplantation (12).…”
Section: Discussionmentioning
confidence: 99%